1994
DOI: 10.1063/1.355731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation ambient on the dielectric breakdown characteristics of thermal oxide films of silicon

Abstract: This study investigated the dielectric breakdown characteristics of thermal oxide films grown by dry and wet oxidation. Oxide films grown by wet oxidation have lower B-mode failure rates and higher B-mode breakdown fields. On the other hand, the reliability of C mode of oxide films does not differ consistently behveen films grown by dry and wet oxidation. These results indicate that as-grown defect causing B-mode failure may shrink or be reduced during wet oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…One of the most characteristic features of this degradation is its oxide thickness dependence: lower breakdown fields for thicker oxide films in the range of 10-50 nm as reported by Murakami and co-workers. 8 As shown in Figs. 17͑a͒ and 17͑b͒, the present reference wafers have a similar oxide thickness dependence.…”
Section: E Degradation Due To Grown-in Defectsmentioning
confidence: 79%
See 2 more Smart Citations
“…One of the most characteristic features of this degradation is its oxide thickness dependence: lower breakdown fields for thicker oxide films in the range of 10-50 nm as reported by Murakami and co-workers. 8 As shown in Figs. 17͑a͒ and 17͑b͒, the present reference wafers have a similar oxide thickness dependence.…”
Section: E Degradation Due To Grown-in Defectsmentioning
confidence: 79%
“…Metallic contaminants picked up during the fabrication of an integrated circuit degrade the breakdown field of a SiO 2 film, 1-4 as do crystal lattice defects [4][5][6][7][8][9] and roughness of the wafer surface. 10 Although this degradation has been the subject of a large number of studies, it is still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care must also be taken when comparing data to specify gate oxide polarity, substrate type, and whether dc, pulsed, or ac stress conditions have been used [256,265,625,628,748,[814][815][816][817][818][819][820]. Much effort has gone into production of extremely uniform and reliable oxides [223,261,676,[821][822][823][824][825][826][827][828][829][830][831][832][833][834].…”
Section: Reliabilitymentioning
confidence: 99%
“…[5][6][7] We have reported that, under the positive gate stressing ͑Fowler-Nordheim electron injection condition from the inversion layer͒, Q bd in wet oxides is larger than that in dry oxides, irrespective of temperature, and that the activation energy E a of Q bd in the high temperature region is the same ͑around 0.1 eV͒ for both oxides. 7 We have proposed that the origin of this E a can be ascribed to diffusion of hydrogen related species, which are responsible for dielectric breakdown in the high temperature region, because the activation energy of diffusion of atomic hydrogen has been reported to be 0.18 eV.…”
Section: Correlation Between Two Dielectric Breakdown Mechanisms In Umentioning
confidence: 99%